THE EFFECT OF OCEANOGRAPHIC FACTORS ON SKIPJACK TUNA FAD VS FREE SCHOOL CATCH IN THE BONE BAY, INDONESIA: AN IMPORTANT STEP TOWARD FISHING MANAGEMENT - Mukti Zainuddin; . Safruddin; Muhammad Ridwan; Andi Rani Sahni Putri; Rachmat Hidayat (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
The aims of this study were to compare skipjack catch between FAD and free school fishing grounds and to describe the effect of the oceanographic factors on either skipjack tuna Fish Aggregating Device (FAD) or free school.  We used a field survey method for collecting the skipjack catch and the fishing positions for both near FAD and free school areas.  Remotely sensed satellite data of sea surface temperature (SST) and chlorophyll-a concentration (Chl-a) were also used to extract the oceanographic data corresponding with both the fishing locations. To find out the vital oceanographic factors, we examined the characteristics of the oceanographic variables and skipjack catch using t-test. Results indicated that the fishing operations of skipjack tuna at FAD tended to locate areas of relatively higher Chl-a than at free school locations. We also found that skipjack tuna catch was higher near the FAD than the other area, where the Chl-a was the most significant factor that affected the difference. This study suggests that the number of skipjack tuna FAD in the coastal waters of Bone Bay should be calculated accurately to ensure and support the tuna fishing management in that study area.